Microscopy of maize grains subjected to continuous and intermittent drying - Geraldo Acácio Mabasso; Valdiney Cambuy Siqueira; Wellytton Darci Quequeto; Osvaldo Resende; Vanderleia Schoeninger; Elton Aparecido Siqueira Martins; Eder Pedroza Isquierdo (Acta Scientiarum: Agronomy, 2022)
Drying is an important step in the post-harvest processes as a way of product conservation and quality preservation. In this context, this study aimed to evaluate the effect of continuous and intermittent drying of maize grains with different rest periods on the integrity of their micro- and macroscopic structures. Maize grains were harvested with a moisture content of 0.3399 ± 0.001 dry basis (db) and subjected to continuous and intermittent drying with 4, 8, 12, and 16 hours of rest period. An experimental fixed-bed dryer, with controlled drying air conditions at a temperature of 100 °C and air flow of 1.5 m3 min.−1 m−2 (12 m3 min.−1 m−3), was used. Continuous drying was completed with a moisture content of 0.1628 ± 0.0003 db, whereas intermittent drying was interrupted with 0.2195 ± 0.0002 db and resumed after rest. The drying rate, integrity through grain images, the conformation of particles through scanning electron microscopy, and cell membrane integrity were evaluated. The drying rate increased with an increase in the rest period, the increase in rest period reduced the intensity of cracks, and the reduction in rest period led to higher dispersion and reduction in the size of starch granules and lower integrity of cell membranes.